STUDY OF OUTWARD SIGNS, MICROSCOPY AND CHEMICAL COMPOSITION OF WALNUT - Av, Strelyaeva; Di, Lezhava; An, Luferov; Nv, Bobkova; Nv, Kartashova; Rm, Kuznetsov (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Walnut is a medicinal plant that is widely used in traditional medicine. We believe that the study of the medicinal plant material of walnut-fruit in the stage of milky-wax maturity and walnut bark is relevant. We described outward signs and microscopy, the diagnostic features of both whole and grinded raw materials, powder bark of walnut and fruits of walnut in the stage of milky-wax maturity. Methods: Alcohol extraction which was derived from walnut bark is a transparent liquid of brown color and alcohol extraction which was derived walnut fruits in the stage of milky-waxy maturity is a transparent, green-brown liquid with a fragrant smell. We performed thin-layer chromatography for the walnut cortex and identified gallic acid. Results: A method of chromatography-mass spectrometry in alcohol extraction from walnut fruit in the stage of milky-waxy maturity allowed to identify 17 compounds belonging to different classes of biologically active substances. We identified sugars, flavonoids, phenolic compounds of coumarins and organic acids. In alcohol extraction from the walnut bark we identified marker substances.